Pendampingan Kesehatan Reproduksi Remaja, Upaya Mencegah Pernikahan Dini pada Masyarakat Petani Desa Sapih Kabupaten Probolinggo - Faisal Faliyandra; Khoiriyah Khoiriyah; Bagus Cahyanto; Fijriah Oktavia Irsadi (GUYUB: Journal of Community Engagement, 2024)
The low level of understanding of public health is one of the factors in the practice of early marriage. This community service purposes to address the problem of understanding early marriage, from a health perspective for students in SMPN IV Lumbang Satu Atap in the farming community of Sapih Village, Lumbang District, Probolinggo Regency. The Service Learning method used socialization focusing on health issues, and the pre-test and post-test are used to see students’ and parents’ understanding. The results show that socialization can solve the problem of students’ and parents’ understanding of the impact of erly marriage from a health perspective. The contextual delivery of material becomes the subject of discussion when implementing it  outreach to farming communities in rural areas.